2021
DOI: 10.1155/2021/6614574
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Suppresses the Proliferation and Migration of Human Lung Cancer Cells through AMPK‐Dependent NLRP3 Inflammasome Regulation

Abstract: Inflammatory reactions mediated by the NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasome contributes to non-small-cell lung cancer (NSCLC) progression, particularly in patients with bacterial infections. Salidroside (SAL) has recently been shown to suppress lipopolysaccharide- (LPS-) induced NSCLC proliferation and migration, but its mechanism of action remains unclear. It has been shown that SAL improves metabolic inflammation in diabetic rodents through AMP-activated protein kinase- (AMPK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…Consistent with previous reports [9,11,29], SAL directly inhibits the proliferation of tumor cells and induces tumor cell apoptosis, suggesting that SAL is an ideal drug for antitumor therapy. Moreover, SAL directly inhibits the proliferation of tumor cells [9,11,29] and regulates the activity and function of immune cells in the tumor microenvironment. In the mouse model of lung injury, SAL also regulated the secretion of in ammatory factors and the number of neutrophils and macrophages, further protecting LPS-induced lung injury [35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous reports [9,11,29], SAL directly inhibits the proliferation of tumor cells and induces tumor cell apoptosis, suggesting that SAL is an ideal drug for antitumor therapy. Moreover, SAL directly inhibits the proliferation of tumor cells [9,11,29] and regulates the activity and function of immune cells in the tumor microenvironment. In the mouse model of lung injury, SAL also regulated the secretion of in ammatory factors and the number of neutrophils and macrophages, further protecting LPS-induced lung injury [35].…”
Section: Discussionsupporting
confidence: 91%
“…SAL on anticancer decreases proliferation and induces apoptosis in A549 cells through its ability to inhibit oxidative stress and p38 [10]. It also suppresses the proliferation and migration of human lung cancer cells through AMPK-dependent NLRP3 in ammasome regulation [11]. Previous studies have shown that SAL regulates the immune response [12].…”
Section: Introductionmentioning
confidence: 98%
“…Its molecular formula and molecular weight are C 14 H 20 O 7 and 300.3, respectively [ 19 ]. Salidroside is documented to have a wide range of pharmacological effects, such as antioxidative, anti-inflammatory, antihypoxic, antifatigue, antidepressive, antiaging, and antitumor properties [ 20 26 ]. Various studies have confirmed that salidroside possesses ameliorative effect on ischemia-reperfusion injury in the heart, brain, liver, and spinal cord [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have shown that salidroside has anti-cancer, anti-apoptosis, anti-virus, anti-depression, anti-osteoporosis and other effects [53][54][55][56][57].…”
Section: Anti-telomere Shorteningmentioning
confidence: 99%